Living, Caring, Learning - Changing mindsets and enabling goals for people with haemophilia - Cruickshank Anne-Louise (The Journal of Haemophilia Practice)
In a nursing career spanning almost five decades, Anne Louise has spent over 30 years caring for people with haemophilia in South Africa. She reflects on the importance of prophylaxis and how tailoring treatment to meet individual needs not only helps to prevent bleeds but can make goals and aspirations attainable. Describing her experience of how she supported a young man with severe haemophilia in achieving his ambition to become a paramedic, Anne-Louise demonstrates the importance of the nurse-patient relationship and the role of the nurse in providing individualised care. She discusses advocating for prophylaxis and the need to change mindsets, and highlights the need for further change in access to treatments for haemophilia in South Africa. The patient also describes his journey to achieving the level of fitness he needed to undertake the entrance exam to train as paramedic.